PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DEPARTEMEN PARTS PT TRAKINDO UTAMA CABANG SAMARINDA - Juliana Juliana (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Individual characteristics and work environment are considered as crucial aspects for companies that want to improve their employees’ performance. PT Trakindo Utama specifically Samarinda branch is one of many branches of PT Trakindo Utama in Indonesia, which become the sole agent of Caterpillar products in Indonesia. Caterpillar itself is the world's leading manufacturer of heavy equipment originally from USA. This research aims to determine the influence of characteristics and non-physical work environment of the employee performance in parts Department at PT Trakindo Utama Samarinda branch. The individual characteristics (x1) and non-physical work environment (x2) are used as independent variables while the performance of employees (Y) as dependent variable. Primary data is obtained by conducting interviews to 34 respondents by using questionnaires while secondary data is obtained by conducting field observation. Data analysis uses a double linear regression technique by using SPSS 22 software. The results show that the individual characteristic variables does not have any partial effect toward the performance of the employees of Parts Department PT Trakindo Utama Cabang Samarinda branch and individual characteristic variables (X1) and non-physical work environment (x2) are simultaneously influential in the performance of the Employees (Y) Parts Department at PT trakindo Utama, Samarinda branch.  Suggestions for PT Trakindo Utama Samarinda Branch, the company should hold a family gathering in order to improve not only for each employees relations but also with bosses to stay awake, provide suggestions and evaluate employee work which can effectively improve employee performance, manage the best possible time so that the job can be completed on time.